THE DICHOTOMY OF EMOTION: DEALING WITH JOY AND SADNESS - Begoyim Abdusattorova; Soliyeva Khusnidabonu (Web of Journals Publishing, 2024)
This study delves into the nuanced expressions of joy and sadness in children aged 6-8 years, exploring the intricate interplay between linguistic acquisition and emotional manifestation. Employing a qualitative descriptive approach, observable verbal and nonverbal cues were analyzed to glean insights into the children's emotional development. Findings reveal a remarkable command over syntactic structures, enabling them to articulate feelings of joy and sadness effectively. Understanding these expressions provides crucial insights for parents, educators, and caregivers, facilitating tailored support during this pivotal phase of growth.
Keywords: Childhood development, emotion expression, psycholinguistics, linguistic acquisition, verbal language, nonverbal communication, syntactic structures, emotional development, joy, sadness, language acquisition, child psychology, emotional intelligence, cognitive development linguistic proficiency.